Second look Percutaneous Nephrolithotomy (PCNL) for residual renal calculi: 3 years experience in Hospital Universiti Kebangsaan Malaysia - Ab Rashid, Islah Munjih; Zainuddin, Zulkifli; Jamaan, Mohd. Nazri (2008)
Presence of residual calculi post PCNL is not rare. Patient might be subjected to a repeat PCNL which is done under general anesthesia, and not without the risk of morbidity. Second look PCNL which is done under local anaesthesia might reduce the chance of a repeat PCNL and its morbidity. The aim of our study is to audit retrospectively the outcome of Second Look PCNL in our institution. Thirty-three patients underwent Second Look PCNL for residual stones from January 2003 to October 2005. The records of each patient are traced and the data is analysed. The stone clearance, tolerability, complication, and operation time are the variables and outcomes studied.The mean age at surgery is 53.3 (24-70). The mean operating time is 43.3 minutes (15-120 min). Out of the 33 patients, 22 patients had their stones completely cleared. Another 10 patients had incomplete clearance which which were successfully treated with extracorporeal shock-wave lithotripsy (ESWL) and didn't need repeated PCNL. ln a patient. we failed to proceed with the second look PCNL due to technical difficulty. As a conclusion, second look PCNL is safe and effective in treating residual calculi post PCNL.